2000
DOI: 10.2460/ajvr.2000.61.1451
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant coagulase-negative staphylococci isolated from healthy horses in Japan

Abstract: Methicillin-resistant coagulase-negative staphylococci that were highly resistant to various antibiotics were isolated from apparently healthy horses in Japan. These organisms must be considered a potential threat to horses and veterinarians who care for them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
4
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 30 publications
3
44
4
2
Order By: Relevance
“…27 In addition, mecA-harboring, coagulase-negative (CoN) staphylococci have been isolated from several domesticated and healthy animals. 14,32 Potential human-to-animal transmission of MRSA has already been reported. 1 Studies in the United Kingdom concluded that MRSA is present in the general horse population and may represent a reservoir of new or rare MRSA strains that could be transmitted to humans.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…27 In addition, mecA-harboring, coagulase-negative (CoN) staphylococci have been isolated from several domesticated and healthy animals. 14,32 Potential human-to-animal transmission of MRSA has already been reported. 1 Studies in the United Kingdom concluded that MRSA is present in the general horse population and may represent a reservoir of new or rare MRSA strains that could be transmitted to humans.…”
mentioning
confidence: 99%
“…3 Furthermore, in Japan, mecA-positive CoN staphylococci were cultured from the skin and nares of healthy horses. 32,33 Recently, high prevalence of the CoN staphylococci was found in healthy horses in Europe. 4,28,26 However, no MRSA strains have been isolated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As the isolate was susceptible to cephalosporins, the antimicrobial treatment did not play any role in selection pressure. In any case, though the origin of mecA is not clear now, the staphylococci harboring mecA was prevalent among not only horses [2,12,14] and chickens [8], but also pigs and cattle in Japan.…”
mentioning
confidence: 99%
“…Selective media containing MPIPC which is incapable of inducing PBP-2' are believed less effective to MRSA of inducing type. For detection of MRSA from foods and animals, a selective medium containing 25 μg/ml CZX had been widely used [8,16,20], but CZX is no longer commercially available. There is a need to develop a new selective medium for effective screening for MRSA including inducible resistance type.…”
mentioning
confidence: 99%